2009
DOI: 10.1007/s00345-009-0416-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-contraction on β-adrenoceptor-mediated relaxation of rat urinary bladder

Abstract: Purpose The human physiological bladder contraction is largely mediated by acetylcholine acting on muscarinic receptors, but in pathophysiological settings the relative role of non-cholinergic stimuli gains importance. -Adrenoceptor agonists are currently in clinical development as treatments for the overactive bladder syndrome. Therefore, we have explored the ability of the -adrenoceptor agonist isoprenaline to induce rat isolated bladder strip relaxation on pre-contraction with the muscarinic agonist carbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 23 publications
7
36
0
1
Order By: Relevance
“…We and others reported previously that CCh-pre-contracted detrusor from many species relaxed less completely with (-)-isoprenaline than KCl-pre-contracted strips [18,19]. In the present study, the relaxation response to (-)-isoprenaline after CCh stimulation was distinctly biphasic, with about equal portions of high and low sensitivity to (-)-isoprenaline (compare table 1).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We and others reported previously that CCh-pre-contracted detrusor from many species relaxed less completely with (-)-isoprenaline than KCl-pre-contracted strips [18,19]. In the present study, the relaxation response to (-)-isoprenaline after CCh stimulation was distinctly biphasic, with about equal portions of high and low sensitivity to (-)-isoprenaline (compare table 1).…”
Section: Discussionsupporting
confidence: 52%
“…While activation of M 3 receptors may counteract β 2 -AR-mediated relaxation by directly stimulating detrusor contractions via enhanced intracellular Ca 2+ release [17], activation of M 2 receptors may oppose relaxation by impairment of cAMP production [20,21]. However, some authors question a dominant contribution of cAMP increase to (-)-isoprenaline-induced relaxation, at least in rat urinary bladder [19]. The nature of the relaxation response with low sensitivity to (-)-isoprenaline is not clear, but non-cAMP-mediated signals could be involved, including the activation of Ca 2+ -dependent BK channels (Ca 2+ -activated K channels of big conduction) [22].…”
Section: Discussionmentioning
confidence: 99%
“…The two studies also involved minor differences in protocol, the most important of which is that study I tested relaxation against basal (passive) tension, whereas study II measured relaxation against KCl-induced tone. Previous studies in rat (Frazier et al 2005;Michel and Sand 2009) and human detrusor strips ) had demonstrated that isoproterenol had a similar potency to induce relaxation against passive tension and KCl-induced tone, although minor numerical differences yielded statistical significance in some cases. While a statistical analysis of observed numerical differences in agonist potency between studies I and II is not meaningful, the potency of both agonists was comparable against passive tension and KCl-induced tone in the present study as well.…”
Section: Critique Of Methodsmentioning
confidence: 88%
“…While mirabegron was consistently less potent than isoprenaline in all three groups, its efficacy was comparable to that of isoprenaline; while the potency of isoprenaline was significantly lower in patients with than without bladder outlet obstruction, smaller numerical differences between groups with mirabegron did not reach statistical significance. In the comparison of these data sets, it should be considered that some experiments were performed against carbacholinduced tone, whereas others were performed against KClinduced tone; a previous work has demonstrated that β-adrenoceptor agonists generally are less potent and less effective against bladder contraction induced by muscarinic agonists than against that induced by KCl (Michel and Sand 2009;Witte et al 2011).…”
Section: Isolated Tissue Studiesmentioning
confidence: 99%